Peranan Program Siaran Kentongan Terhadap Mitigasi Bencana Bagi Pendengar Lembaga Penyiaran Publik Radio Republik Indonesia Banda Aceh - Liani Sisrika Sari; Muzakkir Muzakkir (CV. Publikasi Indonesia, 2022)
The Kentongan Broadcast Program became a disaster management program, especially in Banda Aceh. The Kentongan Broadcast Program has been running for more than two years. The Kentongan Broadcast Program runs from 2019 to the present. After examining what happened, the purpose of this research is to find out how the role of the LPP-RRI Banda Aceh kentongan broadcast program in disaster management. This study uses a qualitative descriptive analysis technique. This research was obtained through interviews. Interviews were conducted using a question and answer process directly with parties who were considered to understand and understand the problem that the researcher was doing. From the results of the research conducted, it shows that the Kentongan Broadcast Program is a disaster response program presented by RRI Pro-1 Banda Aceh at a frequency of 97.7MHz. The Kentongan Broadcast Program contains information on disaster mitigation. The Kentongan Broadcast Program with a duration of 60 minutes is an excellent disaster program at Pro-1 RRI Banda Aceh. The Kentongan Broadcast Program has 2 series of events, namely dialogue inside and outside the studio and interviews of course. and response to disasters. Based on the research results, Radio RRI Banda Aceh plays a very important role in increasing knowledge related to disaster for the community. The role of RRI Banda Aceh can increase public knowledge about disasters.